School practices for newly arrived migrant students: a systematic review of policy enactment - de Fatima Ginicolo, Maria; Dias, Teresa Silva; Neves, Tiago (Frontiers in Education, 2026)
The growing presence of newly arrived migrant students challenges schools to translate integration policies into everyday practice. While the Migrant Integration Policy Index (MIPEX) tracks national frameworks, far less is known about how these policies are implemented at the local level. This systematic review examines how schools support newly arrived migrant students in grades 5–9. Following PRISMA guidelines, we searched Scopus, Web of Science, and EBSCOhost without temporal or geographical restrictions, identifying 35 peer-reviewed studies published between 2009 and 2023. Using an inductive, NVivo-assisted thematic synthesis and drawing on a policy enactment framework, we identified four domains of school practice: (1) reception and family engagement, (2) concentration of migrant students in particular schools, (3) placement in mainstream versus separate classes, and (4) teachers’ classroom practices. Findings indicate that schools act as key mediators that interpret and adapt national guidance to local realities, often innovating through welcoming protocols, intercultural events, and peer tutoring. However, enactment is constrained by limited resources, fragmented initiatives, insufficient teacher training, and unclear policy guidance. The review advances theory by bridging policy enactment with intercultural and critical education, conceptualizing integration as a relational, two-way process rather than a predefined end state. Policy and practice should prioritize targeted funding, sustained professional development in intercultural education, multilingual resources and mediators, and cross-sector partnerships. Because most available peer-reviewed research comes from European contexts, future studies are urgently needed in underrepresented regions—including Africa, Latin America, and Asia—as well as on curriculum adaptation strategies that address cultural and linguistic diversity and on longitudinal evidence examining academic achievement and wellbeing.